Study of Noise in Double and Triple Tunnel Junction Systems (University of Khartoum Engineering Journal, 2022)
Coulomb blockade (CB) and single electron tunnelling (SET) have attracted a lot of attention during the last two decades. Many applications have been proposed and many experimental and theoretical studies were reported. Successful exploitation of Single electron devices requires deep understanding of the physics governing the operation of these devices. Models based on quantum mechanical formulations have been tailored for the study of basic and simple structures with few tunnel junctions. Generalisations of such models are prohibitively cumbersome and have not been attempted. A general purpose semi-classical model has been derived and was successfully used in the study of noise properties in homogeneous long tunnel arrays. In this paper the semi-classical model is used to study the double junction system, known as the single electron transistor. The paper derives closed form finite frequency noise characteristics, together with the zero frequency Fano factor. The model is also used to analyse the dependence of the Fano factor against the applied voltages. It is shown that the IV characteristics and noise measures reveal rich details in the asymmetrical SET as compared to the symmetrical structure. The semi-classical model is also applied to the three-junction system. An analytical expression is derived for finite and zero frequency Fano factor. The model is also used to further the understanding of noise characteristics and the stability of such systems.